The Molecular Mechanisms of Human Osteosarcoma Cell Apoptosis Induced by Arsenic Trioxide and Vincristine - Yao, Xiao-Guang; Zhang, Wei-Hua; Zhao, Gui-Song; Yao, Jia-Chen; Wu, Peng-Huan; Song, Shu-Xia; Liu, Su-Yuan; Arun, Sigdel (Nepalese Journal of Cancer, 2017)
Background: Arsenic trioxide (As2O3) and vincristine (VCR) have been used for the treatment of tumors. But little is known about the mechanisms and whether they induce apoptosis of human osteosarcoma MG-63 cells.Methods: MG-63 cells were treated with As2O3 and VCR, respectively. Their effects on cell apoptosis and cell cycle arrest were evaluated by MTT assay and flow cytometry. Their effects on the expressions of apoptosis-related proteins PCNA, Bcl-2, Bax, caspase-3, cyclin D1 and cyclin E were investigated by Western-blot.Results: Both As2O3 and VCR have time- and dose-dependent effects on apoptosis and cell arrest of MG-63 cells. As2O3 induces MG-63 cell arrest in S phase, whereas VCR induces MG-63 cell arrest in G2/M phase. Both As2O3 and VCR suppress the expression of PCNA, cyclin D1, cyclin E and Bcl-2, and increase the expression of Bax and casepase-3.